Reconsidering IELTS Scores in Vietnamese College Admissions: Links to Academic Success Factors - Phan, Khuc (International Journal of Asian Education, 2025)
The International English Language Testing System (IELTS) has been accepted as a college admission requirement in Vietnam since 2017. However, its use in college admissions surged significantly after the Ministry of Education and Training’s 2023 decision to recognize IELTS scores for high school graduation. This study investigated whether IELTS scores at college admission were related to three factors associated with academic success in higher education: psychological well-being, self-efficacy, and self-confidence in key learning skills. The research involved thirty-six first-year Vietnamese college students who were divided into three groups based on their admission IELTS scores: below 5.5, 5.5 to 6.5, and above 6.5. Analysis of variance revealed no significant differences in the academic success factors among these IELTS groups at admission. The study also examined whether a College Readiness course designed to enhance these academic success factors yielded different outcomes across the IELTS groups. While students improved in course outcomes, these gains generally did not differ significantly among the three IELTS groups, particularly six weeks after the course ended. These findings, combined with the limited research on IELTS score predictive validity in Vietnam, suggest two implications: first, there is a need for more comprehensive research on how IELTS scores relate to academic success factors in the Vietnamese context; and second, institutions may need to reconsider the weight given to IELTS scores in their college admissions processes.